Pengaruh Role Model dalam Membentuk Karakter Mahasiswa FKIP Universitas Sriwijaya - Anggraini, Shintia; Sucipto, Sigit Dwi (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2025)
This study aims to determine the influence of role models in shaping the character of students in the Department of Education, FKIP, Sriwijaya University. A descriptive quantitative approach was used with 84 students of the 2022 intake selected through simple random sampling. Data were collected using a Likert scale questionnaire and analyzed using the Generalized Linear Model (GLM). The results showed that role models have a positive and significant effect on the formation of student character with an influence coefficient of 0.404 or 40.0%. The better the students’ perception of role models, the better their character, especially in integrity, responsibility, discipline, and empathy. These result support Bandura’s Social Learning Theory which explains that role models influence individual values and behavior, as well as Peterson and Seligmen’s Positive Character Theory which emphasizes the importance of role models in helping individuals develop moral virtues and positive character. This study recommends that lecturers, alumni, and seniors play an active role as role models in supporting students to become future educators with character.